2005
DOI: 10.1016/j.neuron.2005.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A Cxcl12-Cxcr4 Chemokine Signaling Pathway Defines the Initial Trajectory of Mammalian Motor Axons

Abstract: Motor neurons, alone among neurons in the vertebrate CNS, extend axons out of the neural tube to innervate peripheral targets. Two classes of motor neurons, termed vMNs and dMNs, extend axons out of the neural tube via ventral and dorsal exit points, respectively, in accord with their homeodomain transcription factor repertoire. Downstream of these transcriptional codes, the cell surface receptors that shape initial motor axon trajectories have not been identified. We show here that the chemokine receptor Cxcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(170 citation statements)
references
References 56 publications
7
160
0
Order By: Relevance
“…Indeed, it is clear that the chemokine SDF-1 and its receptor CXCR4 play an important role in the development of the nervous system and other tissues. In the nervous system, SDF-1/CXCR4 signaling directs the migration of neural stem cells to a number of different parts of the brain (Zou et al, 1998;Bagri et al, 2002;Lu et al, 2002;Stumm et al, 2003) and the DRG (Belmadani et al, 2005) and also plays a role as an axonal guidance cue (Xiang et al, 2002;Arakawa et al, 2003;Chalasani et al, 2003;Lieberam et al, 2005;Pujol et al, 2005). It has also been demonstrated that neurospheres prepared from postnatal brains express CXCR4 as well as other chemokine receptors (Lazarini et al, 2000;Stumm et al, 2003;Ji et al, 2004;Peng et al, 2004;Tran et al, 2004) and that chemokines act as chemoattractants for these cells (Pluchino et al, 2005;Tran et al, 2004Tran et al, , 2005Widera et al, 2004), suggesting that chemokine-mediated effects may also be important in the regulation of adult progenitor cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is clear that the chemokine SDF-1 and its receptor CXCR4 play an important role in the development of the nervous system and other tissues. In the nervous system, SDF-1/CXCR4 signaling directs the migration of neural stem cells to a number of different parts of the brain (Zou et al, 1998;Bagri et al, 2002;Lu et al, 2002;Stumm et al, 2003) and the DRG (Belmadani et al, 2005) and also plays a role as an axonal guidance cue (Xiang et al, 2002;Arakawa et al, 2003;Chalasani et al, 2003;Lieberam et al, 2005;Pujol et al, 2005). It has also been demonstrated that neurospheres prepared from postnatal brains express CXCR4 as well as other chemokine receptors (Lazarini et al, 2000;Stumm et al, 2003;Ji et al, 2004;Peng et al, 2004;Tran et al, 2004) and that chemokines act as chemoattractants for these cells (Pluchino et al, 2005;Tran et al, 2004Tran et al, , 2005Widera et al, 2004), suggesting that chemokine-mediated effects may also be important in the regulation of adult progenitor cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…To our surprise, Shh signaling appeared normal in 26-1 mutants, but motor axons projected their axons dorsally rather than ventrally. At present, only two genes, the chemokine stromal cell-derived factor 1 (SDF1) (Cxcl12) and its receptor Cxcr4, have been shown to have specific roles in governing initial ventrally directed motor axon outgrowth (Lieberam et al, 2005). The 26-1 mutation is in neither of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system modulates cellular events across different phases of the normal brain development (Boulanger, 2009;Deverman and Patterson, 2009), and here we give an overview of key immune influences on postnatal cellular events. With regard to synaptogenesis, the chemokine CXCL12 and its receptor CXCR4 regulate axonal elongation, branching, and pathfinding by modulating neuronal responses to axon guidance cues (eg, Slit-2, semaphorin 3A, and semaphorin 3C; Chalasani et al, 2003;Tran and Miller, 2003), and CXCR4 and CXCL12 mutant mice show disrupted axonal migration (Lieberam et al, 2005). With regard to synaptic refinement, the immune system modulates the strength of neuronal excitatory synapses to stabilize firing in the context of varying neuronal activity (ie, synaptic scaling).…”
Section: Early-life Immune Activation and Brain Developmentmentioning
confidence: 99%